Targeting the Cellular Signaling: BRAF Inhibition and Beyond for the Treatment of Metastatic Malignant Melanoma. (15th December 2011) - Ades, Felipe; Metzger-Filho, Otto
Abstract : Although advances in cytotoxic treatments have been obtained in several neoplasias, in metastatic melanoma there was no drug able to significantly change the natural history of the disease in the last 30 years. In the last decade, translational research identified important mechanisms in malignant transformation, invasion, and progression. Signaling pathways can be abnormally activated by oncogenes. The identification of oncogenic mutated kinases implicated in this process provides an opportunity for new target therapies. The melanoma dependence on BRAF-mutated kinase allowed the development of inhibitors that produced major responses in clinical trials. This is the beginning of a novel class of drugs in metastatic melanoma; the identification of the transduction signaling networking and other "druggable" kinases is in active research. In this paper, we discuss the ongoing research on cellular signaling inhibition, resistance mechanisms, and strategies to overcome treatment failure.